Peran Uvula bifida terhadap pertumbuhan dan perkembangan bicara anak - ERNY; OKKY PRASETYO; AYLI SOEKANTO (Hang Tuah Medical Journal, 2024)
Background: uvula bifida is a congenital abnormality of the oral cavity that has the potential to cause disturbances in the swallowing process and speech disorders. Case: a 4-year-old boy weighing 11kg came with the main complaints of difficulty gaining weight since the age of 1 year and unclear speech. History of frequent choking and difficulty finishing his food portions. Frequent illnesses such as cough and cold. Evaluation of possible tuberculosis and UTI was done and the results were negative. Physical examination found uvula bifida degree 1 and other examinations within normal limits. Conservative management in the form of education on how to feed little but often, chew slowly, liquid food consistency and avoid spicy foods. Avoid talking while eating and supplementation of Fe, Zinc and multivitamins. Parents are expected to always correct unclear speech, regulate breathing when talking and eliminate habits that make children afraid, such as loud voices, scolding. At the next visit, there was a significant improvement in the child's weight and speech. Conclusion: in cases of malnutrition, it is necessary to look for problems with food intake and expenditure, one of which is often overlooked is oral cavity abnormalities such as uvula bifida. Conservative therapy is performed on grade 1 uvula bifida.